Developing Library and Information Science Programmes for Emerging Market in Nigeria in the 21st Century: The Need for Appropriate Entrepreneurial Skills - Bappah , Magaji Abubakar (MiddleBelt Journal of Library and Information Science, 2015)
Tracing the development of library and information science (LIS) education in Nigeria, the paper provides a perspective for developing LIS courses for the emerging job market in Nigeria. Considering the recent happenings in the LIS field which is predominated by advancements in Information and Communications Technology (ICT), the paper argues that the education and training of LIS professionals in Nigeria has to be in such a way that will make them function effectively in the contemporary information society and also to be self reliant whenever the need arises. The LIS curriculum in Nigeria, therefore, has to be in line with the current global trends and at the same time take cognizance of the local situation if Nigerian LIS schools are to leap-frog into the global LIS scene. However, within this context, the paper also discusses some of the major challenges that hinders the development of LIS curriculum in Nigeria which include lack of proper funding, poverty of ICT facilities and low ICT literacy rate etc. the paper concludes by stressing that Nigerian LIS schools must develop courses that are relevant to the emerging market if Nigerian LIS graduates are to be active participants in the contemporary information world and also all relevant stakeholders should be involved in all curricular matters.